2018
DOI: 10.1007/s00404-018-4766-9
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes and superiorities of prophylactic cervical cerclage and therapeutic cervical cerclage in cervical insufficiency pregnant women

Abstract: Our study suggests that, both prophylactic cervical cerclage and therapeutic cervical cerclage reduce the incidence of recurrent abortion or preterm birth and efficiently extend the length of the pregnancy with live births. The prophylactic cervical cerclage has more advantages in operative time, length of hospital stay after surgery, gestational age at delivery, live births and preterm birth. The length of the cervical before surgery is an independent risk factor for pregnancy outcomes when pregnant women app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
3
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 15 publications
3
10
3
4
Order By: Relevance
“…Although previous publications have addressed maternal-neonatal outcomes associated with cerclage, these studies are primarily small cohort studies (ranging from 18 to 166), systematic reviews, or meta-analyses. 4,[7][8][9][10][13][14][15][16][19][20][21][22][23] Second, our study was derived from the U.S. vital statistics data from 2011 to 2013, which represented 83, 86, and 90% of live births in the United States, respectively. Therefore, compared with prior studies with small sample sizes, our study has increased generalizability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although previous publications have addressed maternal-neonatal outcomes associated with cerclage, these studies are primarily small cohort studies (ranging from 18 to 166), systematic reviews, or meta-analyses. 4,[7][8][9][10][13][14][15][16][19][20][21][22][23] Second, our study was derived from the U.S. vital statistics data from 2011 to 2013, which represented 83, 86, and 90% of live births in the United States, respectively. Therefore, compared with prior studies with small sample sizes, our study has increased generalizability.…”
Section: Discussionmentioning
confidence: 99%
“…9,12,14,15 Finally, our study's objective was to look at maternal and neonatal adverse outcomes remote from initial cerclage placement in contrast to most cerclage studies whose objective is to discriminate outcomes with respect to cerclage indication, type, location, and suture material used or to contrast outcomes between cerclage and expectant management, pessary placement, or progesterone supplementation. 4,5,7,8,[12][13][14][15][16][19][20][21][23][24][25] Despite these differences, our findings were consistent with existing data in several ways. For example, we demonstrated a relationship between prematurity (36.0-36.6 for the purposes of our study) and adverse neonatal outcomes, including low Apgar scores and need for assisted ventilation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The success rate of the prophylactic group was higher than the rescue group, similar to previous studies (78% vs 53%). 18,19 For clinical applications, The success rate can apply to counsel the pregnant women who has cervical incompetence and plan to do the cervical cerclage. Early identification of women at risk of cervical incompetence and early treatment will improve outcomes.…”
Section: Median (Iqr)mentioning
confidence: 99%
“…Meta-analyses of trials of cerclage in women with singleton pregnancies who had a short cervix have not shown a significantly lower rate of preterm delivery overall than the rate without cerclage; however, they have shown benefit in the subgroup of women who had a previous preterm delivery. 15 16 17 18 19 Several studies, including three randomized controlled trials, have demonstrated that cervical cerclage placement in women with placenta previa may reduce antepartum hemorrhage and prolong gestation. 20 21 22 The Cochrane Review of Randomized Controlled Trials (Neilson, Issue 4, 2009) concluded that these trials using cervical cerclage in women with placenta previa, collectively show a relative risk (RR) of delivery at < 36 weeks' gestation of 0.45 with cerclage, an average entry to delivery prolongation RR of 0.35 for an interval of < 6 weeks with cerclage, and a RR of blood transfusion of 0.59 for the cerclage group.…”
mentioning
confidence: 99%